مستويات التفكير الناقد وعلاقتها بمتغيري الجنس والفرع الدراسي دراسة ميدانية على عينة من طلبة الصف الثاني الثانوي في مدارس محافظة دمشق الرسمية - منصور علي; علي لينا (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت هذه الدراسة إلى الكشف عن مستوى مهارات التفكير الناقد لدى عينة من طلبة الصف الثاني الثانوي في ضوء متغيري الجنس والفرع الدراسي (علمي ـ أدبي) وتكونت عينة الدراسة من (288) طالباً وطالبة من طلبة المدارس الرسمية في مدينة دمشق، وقد تم استخدام مقياس (واطسن وجلاسر) للتفكير الناقد، وأشارت نتائج الدراسة إلى أن مستوى مهارات التفكير الناقد لدى طلبة الصف الثاني الثانوي في حدود المتوسط (50%) أو يزيد عليه قليلاً في بعض المهارات، وهو أدنى من المعيار المحدد عالمياً (60%) لطالب الثانوي، وأظهرت النتائج عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05) في مستوى مهارات التفكير الناقد لدى أفراد العينة تعزى إلى متغير الجنس، في حين وجدت فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05) في مستوى مهارات التفكير الناقد لديهم تعزى لمتغير الفرع الدراسي (علمي، أدبي) ولصالح طلبة الفرع العلمي. The purpose of this study detects the level of critical thinking skills a sample of students from the second-grade Students in Secondary Schools in Damascus, according of the variables of sex and section course (scientific literature). The sample included (288) students, from public schools in Damascus. Moreover, instruments were necessary to achieve study goals (Watson and Glaser) of Critical Thinking. The most important findings of the study showed that the level of critical thinking skills among students in secondary second grade within the average (50%) or more than a little in some of the skills, which is lower than the standard specified globally (60%) of the student in secondary school, and the results showed no statistically significant differences at the level of significance (0.05) in the level of critical thinking skills of the sex variable, and there were statistically significant differences at the level (0.05) in the level of critical thinking skills according to the variable section course (Science , literary) for students the scientific section.